2015
DOI: 10.1111/1462-2920.12981
|View full text |Cite
|
Sign up to set email alerts
|

Network succession reveals the importance of competition in response to emulsified vegetable oil amendment for uranium bioremediation

Abstract: Discerning network interactions among different species/populations in microbial communities has evoked substantial interests in recent years, but little information is available about temporal dynamics of microbial network interactions in response to environmental perturbations. Here, we modified the random matrix theory-based network approach to discern network succession in groundwater microbial communities in response to emulsified vegetable oil (EVO) amendment for uranium bioremediation. Groundwater micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(166 citation statements)
references
References 65 publications
(122 reference statements)
4
161
0
1
Order By: Relevance
“…The RMT-based approach is a widely used and robust tool for network construction and has been successfully used to construct various networks, including gene regulatory networks (Zhou et al, 2010; Lin et al, 2011, 2013), functional molecular ecological networks (Zhou et al, 2010) and phylogenetic molecular ecological networks (Zhou et al, 2011; Tu et al, 2016). To construct reliable co-occurrence ecological networks, the RMT-based network method was used (Deng et al, 2015), and only OTUs observed in at least 8 of the 12 samples were used for subsequent network analyses. Specifically, the validated pairwise correlations between OTUs were determined based on a Pearson correlation coefficient cutoff of 0.9 and 0.89 that was automatically identified based on RMT for PAB and FLB, respectively, and then was used for network construction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RMT-based approach is a widely used and robust tool for network construction and has been successfully used to construct various networks, including gene regulatory networks (Zhou et al, 2010; Lin et al, 2011, 2013), functional molecular ecological networks (Zhou et al, 2010) and phylogenetic molecular ecological networks (Zhou et al, 2011; Tu et al, 2016). To construct reliable co-occurrence ecological networks, the RMT-based network method was used (Deng et al, 2015), and only OTUs observed in at least 8 of the 12 samples were used for subsequent network analyses. Specifically, the validated pairwise correlations between OTUs were determined based on a Pearson correlation coefficient cutoff of 0.9 and 0.89 that was automatically identified based on RMT for PAB and FLB, respectively, and then was used for network construction.…”
Section: Methodsmentioning
confidence: 99%
“…PAB are usually associated with colloids and algae (Shao et al, 2014) and are considered algae-associated microbes, particularly during algal blooms (Riemann and Winding, 2001; Cai et al, 2013b), that were shown to have positive or negative effects on algal growth (e.g., algicidal bacteria) in a previous study (Berg et al, 2009). Microbes do not live separately but rather interact with each other to form ecological networks and accomplish ecosystem functions (e.g., material and energy flows, ecosystem stability) (Deng et al, 2015; Shi et al, 2016). Therefore, explaining and predicting the variation in network structure are essential parts of microbial ecology (Zhou et al, 2010) and are useful for guiding practical applications, including biodiversity preservation and ecosystem management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, a series of thresholds from 0.30 to 1.00 with 0.01 intervals were applied to the matrix, and only the similarity values above a certain threshold were kept for calculating matrix eigenvalues. The finest threshold was chosen when the nearest neighbour spacing distribution of eigenvalues followed Poisson distribution, which represents specific and nonrandom properties of complex systems (Deng et al, 2012), and meanwhile the threshold should be as low as possible (Deng et al, 2016). Network analyses were performed using an online analysis pipeline at http://ieg2.ou.edu/MENA.…”
Section: Network Analysismentioning
confidence: 99%
“…Previous reports indicated that the presence of SO 4 2− in groundwater significantly influenced the diversity of subterranean microbial communities (Pedersen, Bengtsson, Edlund, & Eriksson, ). Particularly, several sulphate‐reducing bacteria had strong negative interactions with other microorganisms (Deng et al, ). Our results further confirm the effect of SO 4 2− and sulphate‐reducing bacteria on the microbial community.…”
Section: Discussionmentioning
confidence: 99%